2002
DOI: 10.1128/iai.70.7.3592-3601.2002
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Shedding of an Attenuated Strain ofListeria monocytogeneswith a Deletion ofactA/plcBin Adult Volunteers: a Dose Escalation Study of Oral Inoculation

Abstract: Listeria monocytogenes is an intracellular bacterial pathogen which causes bacteremia and has a tropism for the central nervous system and a propensity to cause maternofetal infection. L. monocytogenes has been shown to be an effective prophylactic and a therapeutic vaccine vector for viral and tumor antigens in animal models. L. monocytogenes mutants lacking the ActA protein, which is essential for intracellular movement, are attenuated but retain immunogenicity in mice. Given the pathogenic potential of L. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 62 publications
2
92
0
Order By: Relevance
“…Second, foreign antigens encoded by Lm are efficiently presented by both MHC class I and MHC class II molecules after being processed to peptides [23,24]; as Lm vectors deliver antigens directly to the DC cytosol, both CD8 + and CD4 + antigen-specific T cells can thus be activated [22]. Third, because the natural route of Lm infection involves oral exposure, Listeria-derived vaccine vectors may be given orally [25][26][27][28]. Fourth, evidence with a Listeria vector containing two genes of feline immunodeficiency virus (FIV) showed that pre-existing immunity against Lm does not preclude the generation of immunity to foreign antigens expressed by the Listeria vector [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, foreign antigens encoded by Lm are efficiently presented by both MHC class I and MHC class II molecules after being processed to peptides [23,24]; as Lm vectors deliver antigens directly to the DC cytosol, both CD8 + and CD4 + antigen-specific T cells can thus be activated [22]. Third, because the natural route of Lm infection involves oral exposure, Listeria-derived vaccine vectors may be given orally [25][26][27][28]. Fourth, evidence with a Listeria vector containing two genes of feline immunodeficiency virus (FIV) showed that pre-existing immunity against Lm does not preclude the generation of immunity to foreign antigens expressed by the Listeria vector [28].…”
Section: Introductionmentioning
confidence: 99%
“…As Lm can cause serious infections in neonates, pregnant women and immunocompromised hosts, different attenuation strategies have been considered: a) to delete the Lm actA gene (either alone or with the plcB or inlB genes) so that both intracellular movement and cell-tocell spreading of bacteria is stopped but immunogenicity is maintained [27,29,30]; b) to delete the uvrA and uvrB genes, which encode nucleotide excision repair genes [31]; and c) to delete essential genes in the D-alanine (D-ala) synthesis pathway. We have chosen the latter approach to develop a highly attenuated vaccine vector, called Lmdd.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains questionable whether such strains are suitably attenuated for general use as a vaccine, especially in immunocompromised individuals. One attenuated Lm strain was found to be 1,000-fold less virulent than the WT parent Lm in mice, yet replication within primary infected host cells was identical to the parental strain, raising questions concerning the potential infectious risk to patients after administration (25).…”
Section: Discussionmentioning
confidence: 99%
“…The intracytosolic lifestyle of Lm has prompted the development of several attenuated strains as vaccine vectors (22)(23)(24)(25)(26). However, it remains questionable whether such strains are suitably attenuated for general use as a vaccine, especially in immunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation